Contextualization of Survey Data: What Do We Gain and Does It Matter?. Issue 3 (3rd July 2017) - Wilkinson, Lindsay R.; Ferraro, Kenneth F.; Kemp, Blakelee R.
Abstract : Survey research designs that integrate contextual data have become more prevalent in recent decades, presumably to enable a more refined focus on the person as the unit of analysis and a greater emphasis on interindividual differences due to social forces and contextual conditions. This article reviews varied approaches to contextualizing survey data and examines the value of linking two data sources to respondent information: interviewer ratings and neighborhood information (measured via census tracts). The utility of an integrative approach is illustrated with data from the Health and Retirement Study. The results reveal modest gains by using a contextualized approach but also demonstrate that neglecting contextual factors may lead to misdirected substantive conclusions, especially for older racial and ethnic minorities. To enhance the ecological validity of survey data, investigators should select theoretically-meaningful contextual data for specific research questions and consider cross-level interactions.